Challenges for Plasma-Derived Medicinal Products - Strengers, Paul F.W. (Transfusion medicine and hemotherapy, 2023)
Background: Plasma-derived medicinal products (PDMPs) are medicinal products derived from human plasma, and a number of PDMPs are listed on the WHO Model List of Essential Medicines. These and other PDMPs are crucial for the prophylaxis and treatment of patients with immune deficiencies, autoimmune and inflammatory diseases, bleeding disorders, and a variety of congenital deficiency disorders. The majority of plasma supplies for manufacturing of PDMPs is coming from the USA. Summary: The future of treatments with PDMPs for PDMP-dependent patients depends on the supply of plasma. An imbalance in the global collection of plasma has resulted in regional and global shortages of essential PDMPs. The challenges at different level are mainly related on a balanced and sufficient supply in order to help the patients in need and should be addressed in order to safeguard the treatment with these essential lifesaving and disease mitigating medicines. Key Messages: It is advocated to consider plasma as a strategic resource comparable to energy and other rare resources and to investigate whether for the treatment of patients with rare diseases, a free market of PDMPs has its limitations and special protection measures should be developed. At the same time, plasma collections should be increased outside the USA, including in low- and middle-income countries.